Nonlinear analysis of reinforced concrete structures using thin flat shell elements - Silva,Jordlly Reydson de Barros (2022)
abstract: This paper presents the development of a nonlinear finite element analysis program for reinforced concrete structures, subject to monotonic loading, using thin flat shell finite elements. The element thickness is discretized in concrete and steel layers. It is adopted the Newton-Raphson method, considering a secant stiffness approach for the Material Nonlinear Analysis, based on the Modified Compression Field Model (MCFT), unlike the usual tangent stiffness approach. The original formulation was expanded to also consider the Geometric Nonlinear Analysis, through a Total Lagrangian Formulation. The program was validated through comparison with experimental results, for different structures. It was observed good agreement, besides adequate computational cost.